Nilai Estetika Arsitektur dan Kearifan Lokal pada Masjid Tuha Lam Ura: Kajian Seni Budaya terhadap Sejarah Sumur Tuha Lam Ura - Betesda Br Tumangger; Intan Munisa; Naila Agiska; Nazhifa Akmalia; Rahma Wardani; Sofia Amatillah; Cut Zuriana (Lembaga Pengembangan Kinerja Dosen, 2023)
Aceh has many historical buildings that require accurate documentation, including Mesjid Tuha Lam Ura in Ateuk Monpanah Village, Simpang Tiga District, Aceh Besar Regency, which has been designated as a Cultural Heritage Site. However, many people are still unaware of its existence. The mosque has unique architectural characteristics influenced by India, particularly its roof structure. It is also suspected that the mosque was built during the period of Dutch Indian influence in Aceh. Therefore, studying its architectural characteristics is important to introduce and preserve the mosque. This study aims to identify the architectural characteristics of Mesjid Tuha Lam Ura and examine the factors influencing them. A qualitative method was used to examine the mosque’s architectural expressions. Data were collected through observation, mapping, redrawing, literature studies, historical documentation, and interviews. The findings show Hindu architectural influences, particularly in the overlapping roof structure resembling a shield. The mosque also has walls approximately 60 cm high, functioning as a boundary between the interior and exterior. These characteristics suggest that the original structure may have been adapted from a Hindu temple into a mosque. This research provides information about the mosque’s architectural characteristics and supports its preservation as a historical landmark in Aceh.